Galaxy Quenching with Mass Growth History of Galaxy Groups and Clusters: The Importance of Post-processing - So-Myoung Park; Kyungwon Chun; Jihye Shin; Hyunjin Jeong; Joon Hyeop Lee; Mina Pak; Rory Smith; Jae-Woo Kim (The Astrophysical Journal, 2023)
We investigate the fraction of quenched satellite galaxies in host galaxy groups and clusters using TNG300 in the IllustrisTNG cosmological magnetohydrodynamical simulations. The simulations show that most satellites are quenched after they fall into their final hosts, and that post-processing is a more dominant mechanism of galaxy quenching than pre-processing. We find that the fraction of quenched satellites at z = 0 increases with host mass, which implies that more massive hosts have higher quenching efficiency because they have more massive groups infalling. Furthermore, we find that hosts that have many early-infall satellites show a higher fraction of quenched satellites at z = 0 than those that have many late-infall satellites, which results in a scatter of the quenched fraction of satellites in a given mass range of hosts at z = 0. Our results highlight the significance of the mass of hosts and the different infall times of satellites in understanding galaxy quenching.